2013
DOI: 10.1088/0953-8984/25/16/165901
|View full text |Cite
|
Sign up to set email alerts
|

A first-principles study on the intrinsic asymmetric ferroelectricity of the SrTiO3–BaTiO3–CaTiO3tricolor superlattice at the nanoscale

Abstract: We report a systematic theoretical study on the ferroelectric behavior of ultrathin three-component ferroelectric films, e.g., CaTiO3-BaTiO3-SrTiO3, sandwiched between electrodes. Using first-principles calculations we demonstrate that such structures have intrinsic asymmetric ferroelectricity which is robust even at the nanoscale. In addition, there exists a certain relationship between the polarization directions and geometric stacking sequences of the superlattices. Specifically, the lowest energy states al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…It is also clear that the smallest direct band gap is 2.39eV at the Г point. Our results are in consistency with Please do not adjust margins Please do not adjust margins the band gap of 2.3 eV according to Gao et al, 32 but they didn't show the band structure. Considering that there is no detailed report about the experimental band gap, we compared with the gaps of BaTiO 3 , CaTiO 3 , and SrTiO 3 .…”
Section: Structural and Electronic Properties Of Bt/ct/st Ferroelectrsupporting
confidence: 91%
“…It is also clear that the smallest direct band gap is 2.39eV at the Г point. Our results are in consistency with Please do not adjust margins Please do not adjust margins the band gap of 2.3 eV according to Gao et al, 32 but they didn't show the band structure. Considering that there is no detailed report about the experimental band gap, we compared with the gaps of BaTiO 3 , CaTiO 3 , and SrTiO 3 .…”
Section: Structural and Electronic Properties Of Bt/ct/st Ferroelectrsupporting
confidence: 91%
“…[29] Generally, a ferroelectric state corresponds to a double-well potential profile, whereas a single-well profile indicates the system is in paraelectric state. The λ-method was used, which describes the potential profile of the soft mode distortions with parameter λ, where λ = +1 and −1 correspond to the polarization "up" and "down" states, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the applied potential on the ferroelectricity of BTO was then investigated. The λ ‐method was used, which describes the potential profile of the soft mode distortions with parameter λ , where λ = +1 and −1 correspond to the polarization “up” and “down” states, respectively . Generally, a ferroelectric state corresponds to a double‐well potential profile, whereas a single‐well profile indicates the system is in paraelectric state.…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al's theoretical work [36] demonstrated that the ultrathin three-component ferroelectric films have intrinsic asymmetric ferroelectricity which is robust even at the nanoscale. More interestingly, the asymmetric ferroelectricity would be more obvious when the tricolor superlattice was contacted with ferromagnetic electrode materials such as SrRuO 3 (Fig.…”
Section: Electric Field Control Of Spin Transportmentioning
confidence: 99%